Enhanced wave-absorbing performances of silicone rubber composites by incorporating C-SnO2-MWCNT absorbent with ternary heterostructure. Issue 16 (November 2019) - Zhao, Jia; Lu, Yuanjin; Ye, Wenlong; Wang, Lei; Liu, Bei; Lv, Shanshan; Chen, Lixin; Gu, Junwei
Abstract: SnO2 and amorphous carbon were simultaneously introduced onto the surface of multi-walled carbon nanotube (MWCNT) by a simple and green hydrothermal process followed by heat treatment, finally to obtain the C-SnO2 -MWCNT absorbent with ternary heterostructure. Subsequently, the C-SnO2 -MWCNT/silicone rubber wave-absorbing composites were prepared. XRD, Raman, XPS, SEM, TEM and TGA indicated the C-SnO2 -MWCNT absorbent with ternary heterostructure was fabricated successfully. When the mass fraction of C-SnO2 -MWCNT was 30 wt% and the thickness was 2.65 mm, the minimum reflection loss (RLmin ) and effective absorption bandwidth (EAB) of the C-SnO2 -MWCNT/silicone rubber wave-absorbing composites could reach −53.5 dB and 3.16 GHz, respectively. Excellent wave-absorbing performance was due to the synergistic effect of multiple interface & dipole polarization and conduction loss. Furthermore, the corresponding heat resistance index ( T HRI ) of the C-SnO2 -MWCNT/silicone rubber wave-absorbing composites with 30 wt% C-SnO2 -MWCNT reached 209.9 °C, higher than that of neat silicone rubber (187.4 °C).